EARLY DEVELOPMENTS IN AMERICAN AUDITING. - Moyer, C. A. (The Accounting Review, 1951)
Abstract Recent developments in auditing receive considerable attention from accountants. The literature and other information available, which relates to auditing in the U.S. up to about the beginning of the twentieth century, seem to indicate that auditing was then completing its first major phase of development. It is generally recognized that auditing in Great Britain had been instituted to a great extent by specific statutory requirements. The principal function of an audit was considered to be an examination of the report of stewardship of corporation directors and the most important duty of the auditor was to detect fraud. Although the adoption of sampling procedures probably represented the most important development in auditing, other changes were beginning to appear, as indicated in the preceding references. This development also seems to represent no departure from the point of view of the detailed auditors, for it seems to represent originally a substitute for the enormous quantity of detailed audit work formerly done in audits.